Process Switching and Its Meaning towards Transgender Identity: An SFL Perspective - Marsandi Manar; Sri Mulyati (Scope : Journal of English Language Teaching, 2022)
This SFL study attempts to scrutinise the process-type switching and its underlying meanings in the cyber-based interactive responses towards an issue of transgender. The issue is confined to the suspected genital reconstruction surgery of an Indonesian celebrity that becomes viral and triggers public debate on social media. 254 Indonesian clauses of interactive comments addressing the issue of transgender identity on a YouTube video of more than 2 million views were analysed. Prompting and replying responses were investigated for their categorization of process types by employing the tables of analysis adapted from the experiential meaning framework of Halliday and Matthiessen (2004). The analysis reveals some occurrences of process type switching in the interactive responses among responders in addressing the Indonesian sensitive and viral issue of transgender identity. In responding to the prompting comments, responders tended to employ relational and material clauses to establish values, evidences, and impacts in objective ways while they also used mental and verbal processes to affect one another in subjective ways. This Hallidayan study hints that the process switching among responders in addressing the issue of transgender is associated with the strategies for maintaining and spreading their ideology by confirming, strengthening, adding, and even arguing.